Susceptibility weighted imaging in acute cerebral ischemia: review of emerging technical concepts and clinical applications. Issue 2 (April 2017) - Hsu, Charlie Chia-Tsong; Kwan, Gigi Nga Chi; Hapugoda, Sachintha; Craigie, Michelle; Watkins, Trevor William; Haacke, E Mark
Susceptibility weighted imaging (SWI) is an essential magnetic resonance imaging sequence in the assessment of acute ischemic stroke. In this article, we discuss the physics principals and clinical application of conventional SWI and multi-echo SWI sequences. We review the research evidence and practical approach of SWI in acute ischemic stroke by focusing on the detection and characterization of thromboembolism in the cerebral circulation. In addition, we discuss the role of SWI in the assessment of neuroparenchyma by depiction of asymmetric hypointense cortical veins in the ischemic territory (surrogate tissue perfusion), detection of existing microbleeds before stroke treatment and monitoring for hemorrhagic transformation post-treatment. In conclusion, the SWI sequence complements other parameters in the stroke magnetic resonance imaging protocol and understanding of the research evidence is vital for practising stroke neurologists and neuroradiologists.